Design and Development of a Pneumatically Actuated Gravity Casting Machine for Aluminum Component Manufacturing - Nur Wahid Panji Anggoro; Bagus Wicaksono; Sutimin (Multidisciplinary Innovations and Research in Applied Engineering, 2025)
Gravity casting using permanent metallic molds is widely adopted in small- and medium-scale foundries for producing aluminum components; however, the manual mold assembly and part-removal steps that characterize conventional practice impose physical constraints on cycle consistency, operator ergonomics, and achievable throughput. This paper presents the design and development of a pneumatically actuated Gravity Casting Apparatus Machine intended to overcome these limitations in the production of aluminum motorcycle accessory components at DTech Engineering, Ltd. The design process followed a structured engineering approach comprising problem identification, functional requirement formulation, CAD-based conceptual modeling using Autodesk Fusion 360 learning edition, component and material selection, and mechanical design calculation. The resulting machine integrates eight principal subsystems: a rigid base plate, precision S45C steel rail shafts, a pneumatically driven movable base plate, a two-part permanent mold fabricated from 40 mm iron plate, an automated ejector plate, a pneumatic air cylinder operating at 6 bar, a structural support table, and an electrical control panel with solenoid-based sequencing. Design calculations addressed pneumatic actuator sizing, rail shaft deflection under mold loading, thermal expansion of mold components, and structural safety factors. Material selection was governed by the dual requirement of mechanical rigidity and resistance to thermal deformation from the molten aluminum environment. Implementation of the machine reduced cycle time from 3.0 minutes per part to 1.24 minutes per part, confirming the validity of the design approach. The study provides replicable design guidelines for foundries seeking to modernize gravity casting operations through low-cost pneumatic automation. Quantitatively, the cycle time decreased by 58.7%, from 3.00 min/part to 1.24 min/part, increasing the estimated production capacity from 20.0 to 48.4 parts/h. The selected 100 mm bore and 25 mm rod double-acting cylinder provides theoretical closing and opening forces of 4.71 kN and 4.42 kN, respectively, at 6 bar.